Studi Perilaku Kegagalan Sambungan Las Tipe TConjunctions Pada Baja Karbon Rendah Dengan Pendekatan Experimen dan Numerik - Mohammad Badaruddin (JURNAL MECHANICAL, 2011)
This research is conducted to investigate failure behavior of welding structure in T-conjunctions type. Welding joint failures were analyzed by both experimental and finite element analysis (2D) approach in terms of stress intensity factor mode I (KI). The stress at the welding zone was strongly influenced by specimen geometries and the ratio of L/h1. The stress intensity factor (SIF) was increased significantly. Whereas, the minimum SIF of specimen #X1 and #Y3 are 58 MPa.√m and 165 MPa.√m, respectively. Failure of welding specimen was more dominated in the zone with the highest stress concentration and also affected by material discontinuity at which the stress was not generated continuously, but localized in any certain area. Specimen without welding did not yield a maximum stress. However, plastic zone formation locally decreases the stress concentration. Discontinuity in the welding specimen does not give rise to plastic stream, thus it will raise the stress concentration at the welding extension region. Discontinuity can be observed by the Von Misses stress pattern at stress welding zone for the welding specimen whereas the specimen without welding was only occurred near the extension zone. Keywords : T-type conjuction welding, stress intensity factor  (SIF), Von Misse stress